2017
DOI: 10.1111/anu.12481
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility coefficients of animal and plant feed ingredients for juvenilePseudobagrus ussuriensis

Abstract: A study was conducted to determine apparent digestibility coefficients (ADCs) of dry matter (DM), crude protein (CP), lipid, gross energy, phosphorus and amino acids (AAs) from Peruvian fish meal (PFM), native fish meal (NFM), meat bone meal (MBM), dried daphnia meal (DDM), soybean meal (SBM), full-fat soybean (FSBM), cottonseed meals (CSM), rapeseed meal (RSM) and corn gluten meal (CGM) for Pseudobagrus ussuriensis (7.8 ± 0.06 g). Test diets were formulated to contain a 70:30 mixture of reference diet to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Furthermore, the muscle thickness of the distal intestine was also affected by 11S. The thickness of the intestinal muscle layer can reflect the peristaltic ability of the intestine, thereby preventing the occurrence of intestinal diseases to a certain extent ( 49 ). This shows that after adding a high dose of 11S to the feed, the peristalsis of the distal intestine is inhibited, while a low dose of 11S could promote peristalsis of the distal intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the muscle thickness of the distal intestine was also affected by 11S. The thickness of the intestinal muscle layer can reflect the peristaltic ability of the intestine, thereby preventing the occurrence of intestinal diseases to a certain extent ( 49 ). This shows that after adding a high dose of 11S to the feed, the peristalsis of the distal intestine is inhibited, while a low dose of 11S could promote peristalsis of the distal intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative feed raw materials are promising FM replacements in aquaculture feed formulation. As such, numerous studies have reported the effect of alternative raw materials on fish growth performance and nutrient digestibility [2,39,[44][45][46][47]. Due to the microbiome being an emerging field of research, the effect of alternative feed raw materials on fish intestinal microbiota is yet to be thoroughly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent digestibility was determined according to the method of Bu et al () and Che et al (). Chromium oxide (Cr 2 O 3 ) was a component of diets as an inert indicator to estimate the apparent digestibility coefficient of nutrients in diets.…”
Section: Methodsmentioning
confidence: 99%